(untitled) (Contemporary Journal of Social Science Review, 2025)
The study examines the impact of consumption-based and production-based carbon emissions on tourism development in Pakistan from year 2000 to 2024. Using Autoregressive Distributed Lag (ARDL) and Nonlinear ARDL (NARDL) models, the research examines environmental and macroeconomic factors such as CBCE, PBCE, economic growth, inflation, and exchange rate. The results support the Growth-Led Tourism Hypothesis, indicating that economic growth significantly influences tourism development. However, CBCE and PBCE show asymmetric effects, with increases in carbon emissions associated with a decline in tourism activity, while reductions do not significantly improve growth. Inflation and exchange rate volatility also negatively influence tourism performance. The findings suggest that sustainable tourism development in Pakistan requires policy action, including reducing industrial carbon emissions, promoting eco-tourism, and maintaining macroeconomic stability. Policymakers should focus on improving environmental regulations, encouraging ecotourism, and lowering emissions through cleaner technologies. Sustainable tourism plans that combine macroeconomic stability and environmental preservation are crucial for long-term growth and support for Pakistan’s sustainable development goals.